1989
DOI: 10.1302/0301-620x.71b3.2722951
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete ruptures of the anterior cruciate ligament

Abstract: In a prospective study, 41 consecutive patients with a partial tear of the anterior cruciate ligament, diagnosed by arthroscopy, were reviewed after an average of 17 months, having been in plaster for six weeks after injury. Their average age was 29 years and review included clinical examination, measurement of anterior and posterior laxity with the Stryker knee laxity tester as well as evaluation of knee function and activity level. Twenty-one patients had unstable knees at follow-up; the mean total anteropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 0 publications
0
47
0
6
Order By: Relevance
“…In two prospective studies of patients with partial ACL teams diagnosed at arthmoscopy, instability on follow-up examinations was present in 51 % and 62% of cases [5,6] …”
Section: Resultsmentioning
confidence: 99%
“…In two prospective studies of patients with partial ACL teams diagnosed at arthmoscopy, instability on follow-up examinations was present in 51 % and 62% of cases [5,6] …”
Section: Resultsmentioning
confidence: 99%
“…Other groups have found good diagnostic ability for laximetry when combined with the pivot-shift test, and there is also suggestion that force-displacement curve analysis could be promising for diagnosis severity [19,78]. Arthrometry may also be useful for monitoring of conservatively treated partial ACL tears, with some evidence that increasing laxity can predict poorer outcomes and therefore guide treatment [93,94].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…This meant that completely normal ligaments (typically in knees with minimal deformity) and attenuated ligaments were both pooled in the "intact" group. In theory, it would have been possible to use a 3-level classification system in which thinned or attenuated ligaments formed a separate group, as proposed by previous authors for acute ACL injuries in adults [26][27][28] and children [29]. However, studies by Waldstein et al [30] and Johnson et al [31] have shown that MR imaging may be necessary to adequately and reliably characterize the integrity of the ACL.…”
Section: Discussionmentioning
confidence: 99%